Dynamic reaching in infants during binocular and monocular viewing - Ekberg, Therese L. (2013)
This study examined reaching in 6-, 8-, and 10-month-olds during binocular and monocular viewing in a dynamic reaching situation. Infants were rotated toward a flat vertical board and reached for objects at one of seven positions along a horizontal line at shoulder height. Hand selection, time to contact the object, and reaching accuracy were examined in both viewing conditions. Hand selection was strongly dependent on object location, not infants’ age or whether one eye was covered. Monocular viewing and age did, however, affect time to object contact and contact errors: Infants showed longer contact times when one eye was covered, and 6-month-olds made more contact errors in the monocular condition. For right hand selection, contact times were longer when the covered right eye was leading during the chair rotation. For left hand selection, there were no differences in contact time due to whether the covered eye was leading during rotation.